当前位置:首页 >> 数学 >>

SCHUR不等式例题


a, b, c, are non-negative reals such that a+b+c=1. Prove that a3+b3+c3+6abc≥1/4 Solution. Multiplying by 4 and homogenizing, 4×(a3+b3+c3+6abc)≥4×(1/4) 4×(a3+b3+c3+6abc)≥1 we seek 4a3+4b3+4c3+24abc≥(a+b+c)3 (a+b+c)3=a3+b3+c3+3a2(b+c)+b2(c+a)+c2(a+b)+6abc a3+b3+c3+6abc≥a2(b+c)+b2(c+a)+c2(a+b) Recalling that Schur’s inequality gives a3+b3+c3+3abc ≥ a2(b+c)+b2(c+a)+c2(a+b), the inequality follows. In particular, equality necessitates that the extra 3abc on the left is 0. Combined with the equality condition of Schur, we have equality where two of a, b, c are 1 and the third is 0. This is a typical dumbass solution. 2 Solution 2. Without loss of generality, take a ≥ b ≥ c. As a+b+c=1, we 1+c≤3 or 1?3c≥ 0. Write the left hand side as (a+b)3?3ab(a + b ? 2c) = (a + b)3 ? 3ab(1 ? 3c). This is minimized for a ?xed sum a + b where ab is made as large as possible. As by AM-GM (a + b)2 ≥ 4ab, this minimum occurs if and only if a = b. 3 2 Hence, we need only consider the one variable inequality 2 1?c + c3 + 6 1?c c = 2 2 1 · (9c3 ? 9c2 + 3c + 1) ≥ 1 . Since c ≤ 1 , 3c ≥ 9c2 . Dropping this term and 9c3 , the 4 4 3 inequality follows. Particularly, 9c3 = 0 if and only if c = 0, and the equality cases are 1 when two variables are 2 and the third is 0. This solution is of the smoothing variety in that we moved two variables together while preserving their sum. In other inequalities √ we may wish to preserve products and thus analyze the assignment a = b = ab. These are both representative of the technique of mixing variables, in which two or more variables are blended together algebraically as part of an argument allowing us to outright equate variables


相关文章:
不等式知识
不等式知识 目录: 三道小题 (一)一些基础。 。。 (二)不等式的一些直观...四次 Schur 是一个强度一般的结论,我们提出了一些补充: 三元四次完全对称不...
2013竞赛专题——著名不等式汇集
2​0​1​3​竞​赛​专​题​—​—​著​名​不​...贝努利不等式 6. 琴生不等式 7. 含有绝对值的不等式 8. 舒尔不等式 9. ...
3.2舒尔不等式和缪尔海德定理(10页)
3.2舒尔不等式和缪尔海德定理(10页)_数学_高中教育_教育专区。3.2 舒尔不...舒尔不等式的若干例题 1244人阅读 2页 免费 不等式同步练习5(均值定... 549...
数学不等式(竞赛)
舒尔( Schur )不等式 设 x , y , z ? R ,则 x ( x ? y )( x ...c c ?1 由题设条件 xyz ? 1 得 abc ? ( a ? 1)( b ? 1)( c ...
关于“矩阵的行列式不等式”的几点注记
阐述其行列式不等式,同时对有些命 题作出了引申与进一步说明;针对复正定矩阵,给出了三个命题,在这三个命题的证明过程 中用到了 Schur 定理和 Holder 不等式。 ...
不等式理论简史
从此不等式不再是一些零星散乱 的、孤立的公式综合, 它已发展成为一套系统的科学...Polya(1926),Mulhoand(1928,1931),Owen(1930),Polya 和 Szegb,Schur(1911)...
数学竞赛中的不等式研究方
3 xyz 由 Schur 不等式可得: x 2 y + xy 2 + x 2 z + xz 2 + y...b ≤3 (2007 年第 48 届 IMO 预选题) 证明:令 x = a+ b? c b+ c...
第三讲:几何不等式(吴跃生)
2 ( ) 在本节例题习题中, 为证明方便计, 仅考虑 △ ABC 的各内角都...Schur 不等式) ( 今日推荐 160份文档 四级养生 中医养生与保健 中医养生...
成开华--不等式
5.Schur 不等式:设 x, y, z≥0, r 是实数,则 xr(x-y)(x-z)+yr(...(1)设 a, b>0,且 a+b=ab,证明: 题) (2)求函数 y= x+27+ 13-x...
矩阵不等式
矩阵不等式_理学_高等教育_教育专区。矩阵不等式,...思考题:对于(1)式,利用定理推导的类似 技术,求出...(Schur’s inequality) 设 A=(ars)∈Cn×n 的...
更多相关标签: